3PL provider selection by AHP and TOPSIS methodology. Issue 1 (5th February 2018) - Bianchini, Augusto
Abstract : Purpose: The purpose of this paper is to provide a two-phase analytical hierarchy process (AHP) and the technique for order preference by similarity to ideal solution (TOPSIS) approach that is a multi-criteria decision-making methodology (MCDM) in the evaluation of third-party logistics (3PL) providers. Design/methodology/approach: After the description of the selection criteria of 3PL providers that are determined by company management, the weights of criteria are calculated by applying the AHP method. The TOPSIS method is then employed to achieve the final ranking results. A sensitivity analysis is developed for a deeper comprehension of results reliability. Findings: The paper shows the complexity of a real 3PL provider change. At the same time, a simple MCDM methodology is provided to assure the success of this activity in which many other companies have failed. Research limitations/implications: The proposed MCDM methodology represents a very good compromise between a reliable solution and reasonable computational and human effort. 3PL provider selection or change is an extremely complex decision that could be investigated in greater detail with other more complex methodology, with a consequently higher investment, that is not so affordable for all budgets. Originality/value: It is the first time that a two-phase AHP and TOPSIS methodology is applied to an Italian biscuit company for a 3PL provider change together with the analysis of logistics performance after two years. The paper shows a detailed methodology application that could be very useful for managers for their specific application.